THE BEST TEAM WINS : THE NEW SCIENCE OF HIGH PERFORMANCE - Gostick, Adrian Robert
Explains the five disciplines of team leaders, based on the study of more than 850,000 employee engagement questionaires, that result in the most effective and successful workplace teams under contemporary circumstances